iTRAQ-Based Quantitative Proteomics Analysis of HeLa Cells Infected With Chlamydia muridarum TC0668 Mutant and Wild-Type Strains - Wang, Yingzi; Arthur, Emmanuel Wirekoh; Liu, Na; Li, Xiaofang; Xiang, Wenjing; Maxwell, Asamoah; Li, Zhongyu; Zhou, Zhou (Frontiers in Microbiology, 2019)
Chlamydia muridarum, an obligate intracellular pathogen, was used to establish a murine model of female upper genital tract infection by Chlamydia trachomatis. TC0668 in C. muridarum is a hypothetical chromosomal virulence protein that is involved in upper genital tract pathogenesis. The infection of mice with the C. muridarum TC0668-mutant (G216*) strain results in less pathological damage in the upper genital tract. In this study, an isobaric tags for relative and absolute quantitation (iTRAQ)-based quantitative proteomics analysis was performed to identify differentially expressed proteins between TC0668 wild-type (TC0668wt) and TC0668 mutant (TC0668mut) strains at 6, 12, 18, and 24 h post-infection (p.i.). Of the 550 proteins differentially expressed at 18 h p.i., 222 and 328 were up-regulated and down-regulated, respectively, inTC0668mut-infected cells. The expression of seven up-regulated proteins (encoded by SRPRB, JAK1, PMM1, HLA-DQB1, THBS1, ITPR1, and BCAP31) and three down-regulated proteins (encoded by MAPKAPK2, TRAFD1, and IFI16) from the iTRAQ analysis were validated using quantitative real-time (qRT)-PCR. The qRT-PCR results were consistent with those of iTRAQ. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses revealed that the differentially expressed proteins primarily participated in inflammatory responses, fibrosis, metabolic processes, and complement coagulation cascades, and were mainly enriched in the phosphatidylinositol 3′-kinase (PI3K)/Akt, nuclear factor kappa-B (NF-κB), and other signaling pathways. Using western-blotting and immunofluorescence detection, significant differences in activation of the PI3K/Akt and NF-κB signaling pathways were observed between the TC0668wt- and TC0668mut-infected cells. Differentially expressed proteins linked with inflammation and fibrosis were used in a protein-protein interaction network analysis. The results suggest that TC0668 may play a pivotal role in C. muridarum-induced genital pathology by inducing inflammatory responses and fibrosis, which may involve the activation of the PI3K/Akt and NF-κB signaling pathways.